OBSTACLE DETECTION USING THERMAL SENSOR FOR UNMANNED AERIAL VEHICLE APPLICATION - ARYASEPTA HARYADI (NIM : 13205102); Pembimbing : Dr. Ir. Arief Syaichu Rohman M.Sc.; Widyawa, ADIEB
Critical to the more widespread use of UAVs (Unmanned Aerial Vehicle) is making them easy-to-use by non-pilots including scientists, forest fire fighters, law enforcement officers, or military ground troops. One key capability for facilitating ease of use is the ability to detect and avoid obstacles, both natural and man made. Nowadays, the common used sensors to detect obstacle are LADAR, RADAR, and visual-based. Departing from the hypothesis that temperature of obstacles that UAVs commonly encountered (such as trees and buildings) similar to the earth, which is hotter than the sky, the author use a thermal sensor as an obstacle detection sensor. Obstacle detection is done by determining a threshold value to categorize an object as an obstacle or not. From the design and research of the single sensor system, concluded that the obstacle detection using thermal sensors can be done by determining threshold values. Threshold values are determined by the choice of four methods considering compromise between desired accuracy against speed and complexity of the data processing. The next stage is to design a proposal of the obstacle detection sensor configuration to determine which maneuver course should be taken by the vehicle. Proposed configuration uses three sensors and compares their values with the threshold values set. The three sensors system designed is considered capable of being applied on simple UAV operations to detect obstacle and determine maneuver course.